2006
DOI: 10.3168/jds.s0022-0302(06)72163-4
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Variation in Milk Flow Characteristics at Udder and Quarter Levels

Abstract: The aim of this study was to describe and analyze effects of parity, stage of lactation, milkability (3 groups of cows with differing peak flow rates), time of milking, and quarter position on milk production and milk flow measures at udder and quarter levels. Particular emphasis was put on changes to the decline phase and in duration of overmilking. More than 75,800 quarter milk flow curves and more than 19,300 udder milk flow curves obtained from 38 cows throughout lactation were analyzed. Stage of lactation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
82
2
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(107 citation statements)
references
References 21 publications
20
82
2
3
Order By: Relevance
“…Therefore, this study could be considered as direct evidence that milking without pre-stimulation negatively influences the milk flow not only at the beginning of milking but also at the end of milk flow. The longer duration of the decline phase at a quarter level is connected with significantly higher SCC (Tančin et al, 2002(Tančin et al, , 2006. The majority of the machine-induced infections occur near the end of milking and a possible explanation could be taken over from Philpot and Nickerson (1991).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, this study could be considered as direct evidence that milking without pre-stimulation negatively influences the milk flow not only at the beginning of milking but also at the end of milk flow. The longer duration of the decline phase at a quarter level is connected with significantly higher SCC (Tančin et al, 2002(Tančin et al, , 2006. The majority of the machine-induced infections occur near the end of milking and a possible explanation could be taken over from Philpot and Nickerson (1991).…”
Section: Resultsmentioning
confidence: 99%
“…The time of milk flow was adapted from the milk flow graphs made by Lactocorder and represented the time between the start of milk flow and the point when the milk flow approached the x-axis. The duration of single milk flow phases is described by Tančin et al (2006) and in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among other things, the shape of milk flow curves is affected by milking conditions (Rittershaus et al 2002, Sandrucci et al 2007. Tančin et al (2006) reported that morning or evening milking significantly influenced all measured milk flow traits because of different milking intervals. All milk flow measures were higher during morning milking except the duration of incline phase (tAN).…”
Section: Introductionmentioning
confidence: 99%
“…Milk yield, udder health and milkability are important factors which have an impact on the dairy industry in developed countries (Petrovski et al 2006, Tančin et al 2006. Machine milking requires gentle, complete and fast removal of milk from the udder under optimal technical and hygienic conditions to maintain animal health (Bruckmaier & Hilger 2001, Lee & Choudhary 2006.…”
Section: Introductionmentioning
confidence: 99%